Hubungan Preferensi Makanan Asrama Dan Asupan Energi Dengan Status Gizi Siswa Asrama - Dora Efriani Roito Tumangger; Emi Inayah Sari Siregar; Fauzi Romeli; Abdul Hairuddin Angkat (Jurnal Ilmu Kesehatan dan Gizi, 2024)
The problem of adolescent nutritional status is related to meeting nutritional needs. Because adolescence occurs physical growth and body development. The imbalance in nutritional intake depends on the preference factor, level of satisfaction with food choices, which will influence the amount of energy intake consumed in adolescents. The aim is to determine the relationship between dormitory food preferences and energy intake with the nutritional status of boys at the RK Serdang Murni Private School Dormitory. This research was conducted in the RK Serdang Murni private school dormitory, Lubuk Pakam District, Deli Serdang Regency. The main research period was carried out in April 2023. The type of research was a quantitative observational approach using a cross sectional design. The population is all young men at the RK Serdang Murni private boarding school and a sample of the entire population of young men. From the research results, based on the nutritional status of young men, the nutritional status was 10.5% less, the status good was 76.3%, the status was over 10.5%, and the obesity status was 2.6%. Based on food preferences, namely the neutral category 28.9%, the like category 60.5%, and the very like category 10.5%, while the energy intake categories namely low energy intake 23.7%, moderate energy intake 57.9%, and good energy intake 18.4%. From the results of the Chi Square test, there was a relationship between young men's food preferences and nutritional status in the RK Serdang Murni private school dormitory with a value of p = 0.002 and there was a relationship between energy intake and nutritional status in the RK Serdang Murni private school dormitory with a value of p = 0.004.